Survey of ICT and Education in Africa : Republic of Congo (Congo-Brazzaville) Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The Republic of Congo has recently developed an official ICT policy co-ordinated by the Committee for the Promotion of Information Technologies in Congo (COPTIC). One of the priorities is to set up a national plan for ICT infrastructure, the lack of which, along with the high cost of computer products and services, is hindering the development of ICT applications in several social sectors, including education. A recent lowering of custom fees has helped to alleviate the problem somewhat. Several distance education initiatives are being developed to provide students and businesses in the Congo with an opportunity to access advanced quality training.